Preparation and Properties of Poly(vinyl alcohol) Fluorescence Fiber Acetalized with Glutaraldehyde - Yue, H.S.; Deng*, X.H.; Sun, Y.; Deng, X.Q.; Xiao, Y. (Asian Journal of Chemistry, 2014)
Hydrophilic poly(vinyl alcohol) (PVA) fluorescence fiber was formed by dispersing oil soluble fluorescent pigment in PVA aqueous solution and wet spinning. The prepared fluorescence fiber was crosslinked with glutaraldehyde to improve the stability in hot water. Filament strength tester was used to determine the tensile properties of acetalized fiber. The crosslinked fluorescence fibers were observed by hot stage microscope and X-ray diffraction. Hot stage microscope observation revealed that the meltable PVA fluorescence fiber could be transformed into infusible by acetalization. The XRD results showed that the acetalization took place in the amorphous region of the fiber. The transformations of the crystal structures may happen if both the fluorescent pigment and the water get involved in the fiber but have nothing to do with the acetalization of the PVA fluorescence fiber. The fluorescence spectrum indicated a maximum absorption of the crosslinked fluorescence fiber is 373 nm and a maximum excitation wavelength is 494 nm, thereby it demonstrated that the acetalization didn’t damage the fluorescence nature of the fiber. As the acetalization took place in amorphous regionthe process didn’t damage the PVA fluorescence fiber mechanical properties.